Cytokine profiles as markers of disease severity in sepsis: a multiplex analysis - Bozza, Fernando A. (2007)
Fundação Oswaldo Cruz. Instituto de Pesquisa Clínica Evandro Chagas. Rio de Janeiro, RJ, Brasil / Universidade Federal do Rio de Janeiro. Hospital Universitário Clementino Fraga Filho. Rio de Janeiro, RJ, Brasil.